Robust Economic Design of T2 Control Chart in Variable Sampling Interval Schemes - Chalaki, Kamyar; Bazdar, Aliasghar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Recent studies have shown that variable sampling interval schemes are substantially quicker than fixed sampling interval schemes in detecting shifts of process mean. T2 charts are designed under a general assumption which is production processes, considering a single scenario. However, this assumption may be unrealistic in many industrial situations because of multiple scenarios. In this paper, a method has been proposed to conduct the robust economic design of variable sampling interval T2 control chart when there are multiple scenarios. We use the Markov chain approach to derive the model. Five parameters of chart (n, h1, h2, w, k) which minimize the robustness criteria under multiple scenarios are driven using a genetic algorithm. Finally, through a numerical example, we have illustrated the effectiveness of proposed model.